Variability and relationships of morphological and anatomical characteristics of Scots pine needles in the fresh relatively infertile pine site - Tereshchenko, L. І.; Gordiyashchenko, A. Y.; Samoday, V.P. (Forestry and Forest Melioration, 2020)
Introduction Development of the tree assimilation system determines a growth and development of other plant organs. Many researchers have shown in their papers that the features of morphological and anatomical structure of needles are largely dependent on trees’ age and condition, climate and weather, mineral, air and water nutrition, other environmental factors, anthropogenic impact, etc. At the same time, formation of morphological and anatomical characteristics is under genetic control. Current publications in Ukraine on studies of the morphological and anatomical characteristics of Scots pine (Pinus sylvestris L.) assimilation system analyse the needles of trees growing within Small Polissia in infertile pine sites (Zaika & Rudenko 2012) and various forest site conditions (Tereshchenko 2015), those of different categories of resin productivity (Osadchuk 2013), variety trials (Dyshko &Torosova 2017), ecotypes from extreme conditions (Pashkevich 2007). It is relevant to thoroughly study a genetic structure of Scots pine populations and to specify genetic markers of resistance to extreme drought conditions. There is an ongoing search for highly informative markers among the quantitative features of vegetative organs. Marker traits can be used when studying how Scots pine trees adapt to new growth conditions. The variation amplitude of morphological and anatomical characteristics of tree needles within a defined stand has been analyzed partially or insufficiently. The aim of the study was to find markers of tree differentiation based on the findings on the morphological and anatomical characteristics variability of pine needles in the 84-year-old Scots pine stand in the Trostyanets State Forest Enterprise. Materials and Methods The studied stand is located in the south-eastern part of Sumy Region (Forest-Steppe natural zone). We used branches with needles of the trees felled in winter. The branches with 2- and 3-year-old increments were harvested from the middle part of the tree crown. 1–3-year-old needles in 31 trees were studied. The length, width, thickness, surface and cross-sectional areas of the needles were determined. The width and height of the cross section and the central cylinder as well as the number and location of resin ducts were determined in the needle middle part using the ‘Biolam-70’ microscope (80-fold magnification). We used healthy 2-year-old needles to analyse their anatomical characteristics. The shape indices of both the cross section and the central cylinder of the needle were defined as the ratio of height/width. Meteorological data from the Krasnotrostyanetske Branch of URIFFM were used to verify the influence of weather conditions on the size of needles in different years. The obtained data on each quantitative characteristic were statistically processed in Microsoft Excel. The degree of characteristics variation was established by means of the Mamaev’s scale of variability levels (Mamaev 1973). Pearson's linear pairwise correlation coefficients were determined for the studied characteristics. The nature of the relationship between the indicators was determined by graphical and regression methods of analysis. Results The 2-year-old needle length variability was more than that of 1-year-old needles: the variation limits were from 59.3 to 102.4 mm and from 61.8 to 98.3 mm, respectively. The index of 3-year-old needles made from 72.6 to 102.1 mm. The length variability had low and medium levels on the Mamaev’s scale. The length variation among the trees for the 3-year-old needles was higher than that for one- or two-year-old needles. It was established that a needle size growth with age does not directly depend on weather conditions. Two-year-old needles taken for the anatomical study had the following average values: length – 75.8 ± 8.10 mm, width – 1.65 ± 0.12 mm, and thickness – 0.74 ± 0.07 mm. The average surface area of the needles was 304.7 ± 40.4 mm2, and the cross-sectional area was 1.22 mm2. The average number of resin ducks in the needle made 13.8 ± 2.8. The variability of the needle size was low; the variability of the number of resin ducks was average as well as the area value. The average width of the central cylinder was 1.1 ± 0.01 mm and the average height was 0.3 ± 0.03 mm. The index of the central cylinder shape ranged from 0.22 to 0.33 and on average it was 0.28 ± 0.004 mm2 (CV = 7.9%). The ratio of the central cylinder shape index to the cross-sectional shape index of tree needles made 63% (CV = 7%). We assume that this ratio may be used as a marker of the micropopulation level. The average distance between the vascular bundles in the central cylinder was 0.3 ± 0.07 mm. Due to the increased variability of the indicator (coefficient of variation is 24%) it cannot be used as a marker for trees. The average index of the cross-sectional shape for 2-year-old needles made 0.45, varying in trees from 0.36 to 0.50. We caution against using the indicator as a marker for individual trees, however, we recommend testing it as a population marker in provenance trial. Out of the 50 obtained correlation coefficients of anatomical and morphological parameters, the relationship was statistically significant in 30% of the cases. The highest correlation was found between the width of the needle and its cross-sectional area (r = 0.99), between the length of the needle and its surface area (r = 0.83), between the width (also the cross-sectional area) and the width of the central cylinder (r = 0.80). It was found that 99.45% of the total variation in cross-sectional area occurs due to changes in the width of the needle. The study showed that in 68.5% of the cases, changes in the length of the needle account for changes in the surface area of the needle. In four more cases, a statistically confirmed significant relationship was established, but the hypothesis that it is a straight-line relation is wrong. Conclusions The study showed that the difference in length of Scots pine needles of different ages does not relate to weather conditions during needles growth. The amplitude of length variation among trees was higher for tree-year-old needles compared with one- and two-year-old needles. The variation coefficients for most of morphological and anatomical characteristics of tree needles had low and medium levels of endogenous variability, while the indicator of the distance between vascular bundles in the central cylinder had an increased level. The morphological and anatomical characteristics of the needles that differentiate the trees include: the needle length and its cross-sectional area, the needle width and central cylinder width, and the number of resin ducts. The equation is determined and the significance is confirmed for the linear regression of the relationships between the width of the needle and the cross-sectional area (r = 0.99), the length and surface area of the needle (r = 0.83), the width, cross-sectional area and the width of the central cylinder (r = 0.80). The ratio of the central cylinder shape index to the cross section shape index made 63% (CV = 7%). The assumption has been made that this ratio may be used as a marker of the micropopulation level. 3 Figs., 3 Tables, 30 Refs. Key words: Pinus sylvestris L., needle characteristics, shoots, central cylinder, markers, resin ducts.